2022
DOI: 10.1108/jfra-07-2021-0189
|View full text |Cite
|
Sign up to set email alerts
|

Risk management and bank performance: evidence from the MENA region

Abstract: Purpose The credit crunch of 2008 and recent COVID-19 influences underscored the importance of liquidity and credit risk management in businesses and financial institutions. The purpose of this study is to investigate the impact of liquidity risk and credit risk management on accounting and market performances of banks operating in the Middle East and North Africa (MENA) region. Design/methodology/approach This study uses a panel data regression analysis on a sample of 51 listed commercial banks operating in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 61 publications
(118 reference statements)
1
12
0
1
Order By: Relevance
“…They argue that increasing the lending rate will facilitate higher return to asset as the financial institutions will earn higher income from credit. Though this variable was significant in the two regimes, the magnitude was higher before the pandemic than during the pandemic, as reported by Harb et al. (2022).…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…They argue that increasing the lending rate will facilitate higher return to asset as the financial institutions will earn higher income from credit. Though this variable was significant in the two regimes, the magnitude was higher before the pandemic than during the pandemic, as reported by Harb et al. (2022).…”
Section: Resultssupporting
confidence: 58%
“…However, the bank characteristics, such as making agricultural economists or expert loan desk officers for agricultural loans, are statistically significant before the pandemic. However, this result is anticipated in the two regimes (Harb et al ., 2022); the variable was only significant before the pandemic. This is not supported in all literature available to the authors.…”
Section: Resultsmentioning
confidence: 82%
“…For example, while Xiazi and Shabir (2022) reported that the relationship between bank size and financial performance was positive for bank samples covering 85 countries, Aydemir and Guloglu (2017) provided evidence that this relationship was negative for Turkish banks. Apart from these findings, Isik (2017b) and Harb et al (2022) reported that size-performance association follows the inverted U-shaped pattern for Turkish and MENA banks.…”
Section: Regression Resultsmentioning
confidence: 95%
“…Arif and Rehmawati (2018) confirmed that Islamic banks' market share is affected by its default rate measured by NPL. Al Zaidanin and Al Zaidanin, (2021) have reported a negative effect of NPL on bank profitability whereas a study by Harb et al, (2022) found that accounting performance of banks is not effected by credit risk but it has a non-linear relationship with market performance.…”
Section: Emirates Nbd (Enbd)mentioning
confidence: 99%